Effect of physical form and level of alfalfa in corn-based diets for finishing steers - Brandt, Robert T., Jr.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred-eighty British crossbred steers (760 lb) were used in a 3x2 factorially arranged experiment to evaluate the main effects of alfalfa form (chopped hay, dehydrated pellets, or a 50:50 mixture of hay:dehy) and level (5 or 10% of diet DM) on finishing steer performance. Alfalfa (third-cutting, 23.9% CP) was harvested in alternate rows from a common field. No interactions between alfalfa form and level were detected. Steers fed chopped hay or the 50:50 mixture gained faster (P < .05), consumed more feed (P < .05), and had heavier final and carcass weights (P < .05) than steers fed dehy pellets. Steers fed 10% alfalfa gained faster (P < .05), consumed more feed (P < .0003), and had heavier carcass weights (P < .02) vs those fed 5% alfalfa. Feed efficiency was unaffected by alfalfa form or level. Lower feed intakes and numerically higher incidences of liver abscesses indicated less ruminal tactile stimulation and more subacute acidosis for dehy pellets vs hay or the 50:50 mixture and for 5 vs 10% alfalfa, respectively. Positive associative responses of 5.1% (P = .07) on daily gain and 2.9% (P = .11) on dry matter intake suggested that the 50:50 mixture provided enough long particles for adequate rumen function at the alfalfa levels studied. Our results suggests more dehy pellets than chopped hay must be fed to provide similar roughage value.
Keywords: Beef; Alfalfa; Hay; Dehydrated pellets; Finishing diets